Formation of Laws Based on The Omnibus Method that Meet Standards of Meaningful Participation - Marsudi Dedi Putra; Heristiawan Aryo Wirotomo (Journal of Law, Politic and Humanities, 2026)
The formation of laws based on the omnibus method attempts to combine various themes in one law and accelerate the legislative process, but has the potential to reduce the quality of participation. Using a legislative approach, comparative studies, and conceptual, this article analyzes how the concept and practice of community participation and what standards are used as benchmarks for meaningful participation in the formation of laws based on the omnibus method. As a result, a country that adheres to the concept of people's sovereignty must fulfill the principle of openness with community participation as its main pillar. Omnibus as a method in the formation of laws often reaps controversy because it does not provide sufficient public access and participation space for the community. The active involvement of the community and stakeholders or related parties affected to provide input and suggestions through a public consultation mechanism at the stages of submitting draft laws, discussions and joint approvals is a standard of meaningful participation that must be met in the formation of laws based on the omnibus method.